2015
DOI: 10.1111/cob.12125
|View full text |Cite
|
Sign up to set email alerts
|

Flatfoot and obesity in school‐age children: a cross‐sectional study

Abstract: Childhood obesity exerts abnormally high stresses on developing foot structures which can lead to structural deformity of the foot. Screening for foot problems in children with overweight helps detect interior risks restricting normal lifestyle in these individuals. The purpose of this study was to investigate the effects of excess weight on the structure and function of the developing foot in students aged 7-14 years. A total of 667 participants were recruited for this cross-sectional study via a multi-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 52 publications
1
20
1
3
Order By: Relevance
“…La obesidad ha sido considerada un factor de riesgo de presentar pie plano. 6,7,8 Se divide en pie plano flexible, flexible con talón de Aquiles corto y rígido. 9 La prevalencia de pie plano (flexible) en niñas/niños de dos a seis años varía de 21 a 57% y disminuye de 13.4 a 27.6% en la edad escolar y persiste en 3% en la edad adulta.…”
Section: Abstract Introductionunclassified
See 1 more Smart Citation
“…La obesidad ha sido considerada un factor de riesgo de presentar pie plano. 6,7,8 Se divide en pie plano flexible, flexible con talón de Aquiles corto y rígido. 9 La prevalencia de pie plano (flexible) en niñas/niños de dos a seis años varía de 21 a 57% y disminuye de 13.4 a 27.6% en la edad escolar y persiste en 3% en la edad adulta.…”
Section: Abstract Introductionunclassified
“…2 Al momento existen pocos artículos que investiguen la presencia de pie plano y pie cavo simultáneamente, por lo que es conveniente su búsqueda en nuestra población. 5,6,7,8,13 Nuestro objetivo es conocer la frecuencia de alteraciones de la huella plantar en una población mexicana específica; evaluar en este grupo si existe mayor frecuencia de alguna alteración del pie ante sobrepeso u obesidad y mencionar si existe disminución de la presencia de alteración de la huella plantar ante el aumento de la edad del educando.…”
Section: Abstract Introductionunclassified
“…The flat foot can affect gait biomechanics and risk of lower extremity injury [33]. In children, the most common form of flat foot is "the infantile loose foot", caused by various deficits: Insufficient muscle development of the foot, ligamentous laxity, increased adipose tissue, and immature neuromuscular control [34,35]. The foot often plays an important role in physical activity, and is advantageous for a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…The studies carried out in Iran indicate that there are more significant differences in the prevalence of flat feet among children with normal weight, overweight and obese children. Studies have shown that with an increase in body weight there is a greater prevalence of flat feet, which indicates that obesity in childhood can lead to structural changes of the feet, angular deformities and in turn decreased activity, which can lead to pain (Sadeghi-Demneh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%